2020
DOI: 10.3389/fncel.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals the Beneficial Effects of Low Glucose on Neuronal Cell Survival in an in vitro Ischemic Penumbral Model

Abstract: Understanding proteomic changes in the ischemic penumbra are crucial to rescue those salvageable cells and reduce the damage of an ischemic stroke. Since the penumbra region is dynamic with heterogeneous cells/tissues, tissue sampling from animal models of stroke for the molecular study is a challenge. In this study, cultured hippocampal HT22 cells under hypoxia treatment for 17.5 h with 0.69 mM low glucose (H+LG) could mimic ischemic penumbral cells since they had much higher cell viability and viable cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Ischemic stroke is mainly due to insufficient blood supply to the brain caused by cerebral artery occlusion, resulting in local cerebral tissue ischemia and hypoxia. Neuronal cells in the brain tissue exhibit energy or ion pump obstacles [ 4 6 ] and rapidly develop reversible or irreversible neuronal damage; therefore, subsequent reperfusion of acute ischemic stroke is essential for neuronal cell rescue [ 7 ]. However, experimental and clinical evidence has shown that restoration of perfusion, the contradiction of increased damage in the short term, often leads to reperfusion injury [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is mainly due to insufficient blood supply to the brain caused by cerebral artery occlusion, resulting in local cerebral tissue ischemia and hypoxia. Neuronal cells in the brain tissue exhibit energy or ion pump obstacles [ 4 6 ] and rapidly develop reversible or irreversible neuronal damage; therefore, subsequent reperfusion of acute ischemic stroke is essential for neuronal cell rescue [ 7 ]. However, experimental and clinical evidence has shown that restoration of perfusion, the contradiction of increased damage in the short term, often leads to reperfusion injury [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%